Efektivitas Exercise Pada Penyakit Myofacial Pain Syndrome Trapezius Upper Literature Review - Muhamad Fahri Lubis A; Dini Nur Alpiah (JURNAL ILMIAH NUSANTARA, 2026)
Myofascial Pain Syndrome (MPS) is a musculoskeletal condition that commonly affects the upper trapezius muscle, causing pain and limitations in daily activities. Physiotherapy, particularly exercise-based programs, plays a significant role in managing this condition. A literature review of experimental studies and randomized controlled trials indicates that regular exercise is effective in reducing pain, increasing range of motion, and improving functional outcomes. Exercises targeting the neck and shoulder muscles have been shown to reduce trigger point sensitivity and enhance local blood circulation. Furthermore, exercise programs demonstrate effectiveness comparable to other physiotherapy interventions. Therefore, exercise therapy can be considered a safe and effective non-pharmacological approach for the management of upper trapezius Myofascial Pain Syndrome.